FRACTIONAL DIFFERENTIAL EQUATIONS WITH NONLOCAL KATUGAMPOLA FRACTIONAL INTEGRAL - Emin, Sedef (Baku State Univ, Inst Applied Mathematics, 2018)
[Abstract Not Available]
6th International Conference on Control and Optimization with Industrial Applications (COIA) -- JUL 11-13, 2018 -- Baku, AZERBAIJAN
Keywords: Fractional differential equations; Caputo fractional derivative; Katugampola derivative; integral boundary conditions